Z-Selective Dimerization of Aromatic Terminal Alkynes Catalyzed by an Iridium(I)–N-Heterocyclic Carbene–Phosphine System - Forsyth, Calum D.; Kerr, William J.; Paterson, Laura C. (Synlett, 2013)
The development of an iridium-catalyzed regio- and stereoselective dimerization process has enabled the formation of (Z)-enyne products. More specifically, low catalyst loadings of an iridium(I) complex, featuring a bulky N-heterocyclic carbene–phosphine ligand combination, has been successfully employed in this selective head-to-head dimerization of terminal alkynes via C–H activation.
Keywords: alkynes; enynes; dimerization; C–H activation; iridium